Evaluation of diffusion coefficients of n‐type impurities in MBE‐grown BaSi2 epitaxial layers. Issue 12 (4th November 2013) - Zhang, N.; Nakamura, K.; Baba, M.; Toko, K.; Suemasu, T.; Maeda, Yoshihito; Suzuki, Motofumi
Abstract Sb layers deposited on BaSi2 epitaxial films on Si(111) substrates were annealed at different temperatures and durations to evaluate the diffusion coefficients of Sb using secondary ion mass spectrometry with Cs+ ions. The activation energies of lattice and grain boundary diffusions in BaSi2 were found to be 0.64 eV and 1.20 eV, respectively. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)